The relevance of traditional knowledge for modern landscape management: Comparing past and current herding practices in Mongolia - Gantuya Batdelger; Beáta Oborny; Batbuyan Batjav; Zsolt Molnár (People and Nature)
Abstract Traditional ecological knowledge (TEK) is increasingly acknowledged as key to sustainability and to the successful adaptation of local communities to rapid changes. However, implementing TEK is a major challenge in most parts of the world. A book published 80 years ago by Sambuu Jamsran, a Mongolian agricultural minister in the 1930s, provides a unique opportunity to compare the past versus present knowledge and practices of semi‐nomadic herders. Sambuu collected information from highly respected herders during a dialogue workshop about the proper management of herds and pastures. This cooperation between a politician and the herders yielded a valuable collection of ‘best practices’. We aimed to assess the relevance of this traditional knowledge for the successful adaptation of local communities in present Mongolia. We interviewed 31 middle‐aged or older herders about 69 pieces of advice extracted from Sambuu's book. Two questions guided our inquiries: (1) Do you agree with the advice? (2) Do people in your region adhere to it? If so, why, if not, why? Most recommendations were still accepted as valid (77%) by herders; however, only a smaller proportion was followed (49% of all). The interviews revealed some key reasons for the abandonment of certain traditional practices in the post‐1990 era, driven by fast social‐economic changes, even though the herders were aware that the traditional practices were more proper and sustainable. The practices that were abandoned the most were those that required greater time investment, were less compatible with modern lifestyles or needed closer cooperation and better functioning institutions. In conclusion, the Mongolian semi‐nomadic herding system exhibits adaptability to new conditions, but the development of proper new practices by herders or the government may take considerable time. As in many cases around the world, there is a time lag between the changes and the herders' responses to these changes. Herders' TEK has a vital role in developing locally adaptive solutions, while institutions have a critical role in formulating policy that can mitigate the negative impacts of rapid changes while fostering tradition‐based, sustainable and innovative practices for the future.